Pertanggungjawaban Pidana Korporasi Dalam Pengadaan Barang/Jasa Menggunakan Metode Penunjukan Langsung - Wahyudia Pratama; Yoyok Ucuk Soyono (Fakultas Hukum Universitas Islam Malang, 2023)
This paper aims to examine criminal acts in the procurement of goods/services by State-Owned Enterprises by direct appointment and forms of corporate responsibility for these crimes. This study uses a normative juridical method with a conceptual, statutory, and case approach. The problem that often occurs in the procurement of goods/services by direct appointment is the existence of collusion and/or bribery between prospective service providers and budget users or between procurement committees with the aim of personal gain or certain groups. Criminal liability in a corporate crime in the procurement of goods/services by direct appointment such as crimes related to criminal acts of corruption and unfair business competition is subject to principal penalties in the form of fines, confiscation of goods, temporary closure of corporations, closure of companies and revocation of certain rights or elimination of all or part of the profits.